divide the whole equation by 3
(3x-12)/3= x-4
~>
3x-12=(3)(x-4)
2007-02-22 17:48:28
·
answer #1
·
answered by jAmPr0tzz 2
·
0⤊
1⤋
3x-12 = 0
3x = 12
x = 12/3
x = 4
2007-02-22 23:10:35
·
answer #2
·
answered by Archu 2
·
1⤊
0⤋
This is it. 3x - 12 = 3 (x-4)
2007-02-22 19:06:24
·
answer #3
·
answered by pinoy henyo 1
·
1⤊
0⤋
This Site Might Help You.
RE:
how do i factor 3x -12?
2015-08-18 10:05:56
·
answer #4
·
answered by Merrily 1
·
0⤊
0⤋
3(x-4)
NB:if we have to solve for x ;then we can let y=0
then 3x-12=0; then transpose 12 to the other side; devide by 3 and you will get our x=4
2007-02-22 19:58:30
·
answer #5
·
answered by tsm 1
·
0⤊
0⤋
3(x-4)
2007-02-22 18:20:24
·
answer #6
·
answered by S . Sushmita 2
·
0⤊
0⤋
3(x-4)
2007-02-22 17:34:54
·
answer #7
·
answered by Jian C 3
·
0⤊
0⤋
well take out the common factor..i.e. 3
3(x-4)
2007-02-22 17:57:53
·
answer #8
·
answered by Akshav 3
·
0⤊
0⤋